The Role of Neutrophil to Lymphocyte Ratio in Predicting the Response to Neoadjuvant Targeted Therapies in HER2-Positive Breast Cancer: Predictive Value of NLR in HER2-Positive Breast Cancer - Bibi, Maryam; Tariq, Muhammad; Mehmood, Nasir; Malik, Bushra; Alam, Faryal; Hassan, Masroor; Farooq, Qazi Muhammad (Pakistan Journal of Health Sciences, 2026)
The neutrophil-lymphocyte ratio (NLR) is a basic systemic inflammatory biomarker, previously associated with treatment response in different forms of cancer. Its predictive importance on response to neoadjuvant HER2-targeted therapies in HER2-positive breast cancer has not been well-established, especially in Pakistani patients. Objectives: To identify the relationship between pretreatment NLR and response to neoadjuvant HER2-targeted therapy in women with HER2-positive breast cancer. Methods: This was a descriptive study carried out in Khyber Teaching Hospital. Non-probability consecutive sampling was used to enroll 120 patients. Standard neoadjuvant HER2-targeted therapy was given to patients, and after 12 weeks, treatment response was evaluated based on Miller-Payne criteria. SPSS version 25.0 was used to analyze data. Chi-square/Fisher exact tests were used to establish associations between NLR and treatment response, and multivariate logistic regression was used to determine independent predictors of complete response. Results: Out of the 120 patients, 70 (58.3%) patients had low NLR, and 50 (41.7%) patients had high NLR. Full response was obtained in 16 (22.9%) low (NLR) and 4 (8%) high (NLR) (p=0.004) patients, respectively. High NLR was an independent predictor of reduced odds of complete response using logistic regression (p=0.035). Conclusions: A low pretreatment NLR is linked to better response rates to neoadjuvant HER2-targeted therapy, which indicates its potential use as a cost-efficient biomarker in informing decisions on the use of treatment strategies in the management of patients with HER2-positive breast cancer.